Formation evaluation: correlation between clay volume and porosity based on well logging data - Setyowiyoto, Jarot; Samsuri, Ariffin (2008)
Formation evaluation that includes porosity, clay volume and water saturation estimation is very important stage in prospecting for reservoir characterization and hydrocarbon reserve. The logging data studied comprises of gamma ray, electric (spontaneous potential, micro spherical focused, laterolog deep and shallow, formation density and compensated neutron log. The gamma ray log is used to determine lithology, reservoir and non reservoir rocks, facies and depositional environment. Electric logs analyze fluid rock type such as hydrocarbon or formation water. Porosity is calculated by both density and neutron log. The research has been carried out by qualitative and quantitative analysis based on schlumberger method. Porosity is obtained from density log and then corrected by clay volume and hydrocarbon fluid content. Water saturation is calculated based on the true resistivity (Rt), clay volume (Vsh) and corrected porosity (ï¦c) parameters. As a result, the hydrocarbon is trapped in ten porous zones that have the reservoir thickness vary between 10- 140 feet. The highest hydrocarbon saturation occurred in the reservoir-8 that is 71% with water saturation 29%, formation temperature 163.49 deg F, clay volume 19 %, and porosity 25.4%. Oil water contact (OWC) encountered at the 2358 feet depth and underneath this OWC form the depletion zone. The correlation between clay volume and porosity showed that the increasing of clay volume result in decreasing porosity. The water saturation is strongly influenced by the value of resistivity log, increasing of resistivity will results in decreasing water saturation.